THE EFFECT OF THE KLEAR AND DUAL COMPETITIVE LEARNING STRATEGIES ON LEARNING THE EFFECTIVENESS OF LONG JUMP FOR STUDENTS - Assist.lect. Hussein Abdul Sattar Lafta (Proximus Journal Publishing, 2024)
The aim of the research is to prepare two teaching curricula using the Clear and Competitive strategies to teach the effectiveness of the long jump. To know the effect of teaching the klear strategy in learning the effectiveness of the long jump. To know the effect of teaching the Competitive strategy in learning the effectiveness of the long jump. The research community was deliberately selected from the first-year students of the Department of Physical Education and Sports Sciences/College of Basic Education - Al-Mustansiriya University, for the academic year (2024-2024), consisting of (70) students distributed over (5) academic departments. As for the research sample, it was selected randomly from the research community, where (3) departments were selected and by lottery, departments (B, C, D) became composed of (47) students to represent the research sample, ailed students, postponed students, and students of the exploratory experiment were excluded
Keywords: postponed; students; curricula